Batroxase promotes the effect of NK cell adoptive therapy on lung cancer by enhancing immune cell infiltration: Batroxase boosts NK cell therapy in lung cancer - Liu, Xing; Wang, Xiaoyu; Wang, Rui; Shi, Bin (Cellular and Molecular Biology, 2024)
Batroxobin, isolated from Bothrops moojeni, is a defibrinogenating agent used as a thrombin-like serine protease against fibrinogen for improving microcirculation. Here, we investigated whether, and if so, how batroxobin acts in concert with NK cells in terms of anti-tumor effects. CD3+/CD56+ NK cells were isolated and cultured from C57BL/6 mouse spleen. NK cells’ viability was tested via Lactate dehydrogenase (LDH) assay. Lewis lung cancer cell (1*107 cell/ml) was used to build animal models. All animals were divided into five groups and treated with Batroxobin and NK cells respectively. HE staining was used to detect the pathological morphology of tumor tissue. The contents of fibrinogen and TNF-α in serum were determined by ELISA. The protein expression levels of MMP2, MMP9, VEGF and CD44 in tumor tissues were detected by Western Blot or immunohistochemistry. Compared with Control group, Tumor growth was not significantly affected in the group treated with Batroxobin or NK cells alone, However, tumor growth was significantly inhibited in the NK cell combined with the Batroxobin group. Serum levels of Fbg and TNF-αin mice treated with Batroxobin combined with NK cells dropped significantly, bringing them closer to normal levels. WB results showed that the expression levels of MMP2/9, VEGF and CD44 in Batroxobin combined with NK cell group also significantly decreased. Batroxobin combined with adoptive immunotherapy with NK cells significantly inhibited the growth of Lewis lung cancer in mice.